Use of French lyophilized plasma transfusion in severe trauma patients is associated with an early plasma transfusion and early transfusion ratio improvement. Issue 5 (May 2018) - Nguyen, Cédric; Bordes, Julien; Cungi, Pierre-Julien; Esnault, Pierre; Cardinale, Michael; Mathais, Quentin; Cotte, Jean; Beaume, Sébastien; Sailliol, Anne; Prunet, Bertrand; Meaudre, Eric
Abstract : BACKGROUND: Early transfusion of high ratio of fresh frozen plasma (FFP) and red blood cells (RBC) is associated with mortality reduction. However, time to reach high ratio is limited by the need to thaw the FFP. French lyophilized plasma (FLYP) used by French army and available in military teaching hospital does not need to be thawed and is immediately available. We hypothesize that the use of FLYP may reduce time to reach a plasma/RBC ratio of 1:1. METHODS: A retrospective study performed in a Level 1 trauma center between January 2012 and December 2015. Severe trauma patients who received 2 U of RBC in the emergency room were included and assigned to two groups according to first plasma transfused: FLYP group and FFP group. RESULTS: Forty-three severe trauma patients in the FLYP group and 29 in the FFP group were included. The time until first plasma transfusion was shorter in the FLYP group than in the FFP group, respectively 15 min (10–25) versus 95 min (70–145) ( p < 0.0001). Time until a 1:1 ratio was shorter in the FLYP group than in the FFP group. There were significantly fewer cases of massive transfusion in the FLYP group than in the FFP group with respectively 7% vs. 45% ( p < 0.0001). CONCLUSION: The use of FLYP provided significantly faster plasma transfusions than the use of FFP as well as a plasma and RBC ratio superior to 1:2 that was reached more rapidly in severe trauma patients. These results may explain the less frequent need for massive transfusion in the patients who received FLYP. These positive results should be confirmed by a prospective and randomized evaluation. LEVEL OF EVIDENCE: Therapeutic, level IV.